DETERMINATION OF THE MOISTURE CONTENT OF PUMPKIN SEED (Cucurbita moschata) SUBJECTED TO DRYING IN AN OVEN - Santos, Debora Souza dos; Lima, Julio Gabriel Oliveira de [UNESP]; Araujo, Tales de Oliveira; Farias, Fabiana Pimentel Macedo de; Souza, Josedite Saraiva de (Faema-fac Educacao & Meio Ambiente, 2023)
The drying process occurs from the passage of hot air over the food, dragging its moisture with it, physically because of the transfer of mass and energy to the medium. Pumpkin is a food rich in water, vitamin B, C and carotenoids, present in the food itself and in the seed, the latter is a residue at the time of consumption of the fruit that, when dehydrated, can be reintroduced into human food via flour, bread, cookies and cakes. For the process, it was necessary to previously asepsis the biological material and weigh it before going to the oven at temperatures of 70 & DEG;C and 80 & DEG;C, then it was weighed at times of (5-10-15-30-60-120-180) min and then 24h. An initial variation in temperature can be identified up to the first 60 minutes of operation due to the evaporation of volatile substances and thermal equilibrium between the surface of the pumpkin and the environment, in addition to the observation of greater loss of water at a temperature of 80 & DEG;C, in the amount of 56.19%. Due to the high final concentration of moisture in the product, a longer dehydration time or methodological modification is suggested to obtain a higher dehydration rate.
Keywords: Mass Transfer; Dehydration; Conservation